“Talk to the hand”: handling peer conflict through gestural socialization in an elementary classroom - Corella, Meghan (Frontiers in Communication, 2023)
Although researchers of language and communication have become increasingly interested in both embodiment and conflict in recent years, little is known about how elementary students use embodied actions modeled by their teachers as they engage in peer conflicts. This paper addresses such questions, focusing on the “quiet coyote” gesture and the “open hand prone” gesture, two emblems commonly used as classroom management strategies in elementary grades. Building on work in language socialization, gesture studies, and other areas of discourse analysis, I propose what I call a gestural socialization perspective for analyzing the nuanced ways the US second-grade children in this study use and socialize one another to use these gestures, as well as other semiotic resources, to handle peer disputes. An ethnographically informed, multimodal discourse analysis centering on a multiracial group of girls reveals how students’ gesture practices draw on their teacher’s gestural socialization practices while also diverging from them, especially with regard to gestural form, stance object, intended recipient, and accompanying metapragmatic commentary. These aspects of the participants’ appropriations of the “open hand prone” and “quiet coyote” emblems, together with their use of gestural innovations, metagestures, and other semiotic resources, allow them to take more oppositional stances than those made relevant by the teacher’s practices. Through these multimodal stances, students take a hands-on approach to starting, continuing, and closing peer disputes on their own terms. Overall, the study highlights how participants’ handling of disputes often subverted a local emphasis on conflict avoidance, efficiency, and appropriateness and the developmentalist, neoliberal, and standard language ideologies underpinning these norms. The paper closes with a discussion of implications for research and pedagogy, emphasizing the importance of closely attending to the multimodal, interactionally emergent, and culturally situated nature of conflicts among children and people of all ages.